Rethinking project reliability using the ambidexterity and mindfulness perspectives - Turner, Neil; Kutsch, Elmar; Leybourne, S (Emerald, 2016)
Purpose The purpose of this paper is to bring together two seemingly disparate bodies of literature – ambidexterity (the ability both to exploit and explore) and mindfulness – to take a fresh perspective on the management of uncertainty. The authors differentiate between “rule-based” and “mindfulness-based” reliability and explore project risk responses in environments characterised by varying degrees of uncertainty. Design/methodology/approach Five case organisations across a range of industries are used to illustrate how uncertainty may be prepared for and suitable responses activated. This also adds to the understanding of the nature of ambidexterity, which has previously been characterised primarily at the organisational level with relatively few studies looking at managerial actions and “switches” between modes. The data consist of initial survey responses to indicate the level of mindfulness under conditions of normality, followed by interviews studying particular incidents and the nature of the responses. Findings Key practices are identified that support high reliability in complex projects, with four managerial modes (“Traditional”, “Just-in-time”, “Infusion”, and “Entrepreneurial”) that emerged from the data. Practical implications The findings offer managers a practical framework to choose between different modes of reliable performance by considering the uncertainty of the environment and whether the primary driver of the work is efficiency or effectiveness. This allows managers to reflect on their own organisations and practices and identify whether their current approach is suitable. Originality/value This work offers new insight into risk responses in complex environments and shows how the mindfulness and ambidexterity literatures may be used as beneficial lenses to increase understanding. Blending these two schools also offers opportunities for future research.
Keywords: Ambidexterity; Mindfulness; Projects; Reliability; Risk; Uncertainty